Study on inducing twin calves in beef cattle through embryo transfer technology (Mongolian Journal of Agricultural Sciences, 2024)
The low reproduction rate of beef cattle constrains the development of the beef industry. Twin calving has long been a focal point of research due to its potential to enhance reproductive efficiency and increase beef production. In Hohhot, Inner Mongolia, two groups of Simmental cattle were evaluated to assess the effectiveness of twin calving induction through embryo transfer technology and artificial insemination. Group I involved the simultaneous transfer of two embryos, while Group II employed a combined strategy integrating single embryo transfer with artificial insemination. The results showed that 18 out of 22 cows in Group I exhibited estrus, resulting in an 82% estrus detection rate. Subsequently, 14 cows conceived (77.8% conception rate), and 10 delivered twins, resulting in a 71.4% twin rate. In Group II, 45 out of 50 cows exhibited estrus (90% estrus detection rate), 36 conceived (80% conception rate), and 22 gave birth to twins, resulting in a 62% twin birth rate. This study significantly enhances reproductive efficiency in cows and provides valuable technical support for implementing twin calving in beef cattle production.